2016
DOI: 10.1371/journal.pone.0166319
|View full text |Cite
|
Sign up to set email alerts
|

Local Stressors, Resilience, and Shifting Baselines on Coral Reefs

Abstract: Understanding how and why coral reefs have changed over the last twenty to thirty years is crucial for sustaining coral-reef resilience. We used a historical baseline from Kosrae, a typical small island in Micronesia, to examine changes in fish and coral assemblages since 1986. We found that natural gradients in the spatial distribution of fish and coral assemblages have become amplified, as island geography is now a stronger determinant of species abundance patterns, and habitat forming Acropora corals and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 64 publications
3
15
0
Order By: Relevance
“…The present findings corresponded with a complimentary, fisheries‐independent study that reported predator (primarily) and large invertivore and herbivore (secondarily) losses were key drivers of shifting baselines in ecosystem condition between 1986 and 2015 in Kosrae, with declines most pronounced where access to fishing grounds was highest (McLean et al. ). Both studies suggested that similar functional components of the fishery and ecosystem were compromised, helping to identify species that contribute most toward ecosystem‐based management targets.…”
Section: Discussionsupporting
confidence: 88%
“…The present findings corresponded with a complimentary, fisheries‐independent study that reported predator (primarily) and large invertivore and herbivore (secondarily) losses were key drivers of shifting baselines in ecosystem condition between 1986 and 2015 in Kosrae, with declines most pronounced where access to fishing grounds was highest (McLean et al. ). Both studies suggested that similar functional components of the fishery and ecosystem were compromised, helping to identify species that contribute most toward ecosystem‐based management targets.…”
Section: Discussionsupporting
confidence: 88%
“…We therefore hypothesize the replacement of large-bodied species with smaller-bodied counterparts in accordance with trophic position may be more a consequence of fishing pressure and less a consequence of natural factors. In support, this same trend has been observed elsewhere in Kosrae, Micronesia [ 30 , 52 ], and on Guam [ 53 ]. In all these instances, mid-sized species that dominated landings of snappers and groupers had skewed size distributions indicating compensatory density dependence responses.…”
Section: Discussionsupporting
confidence: 88%
“…High waves may provide a refuge from fishing pressure (Branch and Odendaal , McLean et al. ) and flush reefs and mitigate land based source pollution, thus improving habitat quality (Fabricius , ). Highly wave exposed areas also have less small‐scale structure such as from branching corals and support fewer small species, while large fishes are stronger swimmers and thus able to subsist in areas with high wave energy (Friedlander and Parrish , Friedlander et al.…”
Section: Discussionmentioning
confidence: 99%